Stereospecific Biosynthesis of β‐Methyltryptophan from L‐Tryptophan Features a Stereochemical Switch1. Issue 49 (25th October 2013) - Zou, Yi; Fang, Qi; Yin, Haixing; Liang, Zutao; Kong, Dekun; Bai, Linquan; Deng, Zixin; Lin, Shuangjun
<x xml:space="preserve">Abstract</x> Make the switch: The three‐enzyme cassette MarG/H/I is responsible for stereospecific biosynthesis of β‐methyltryptophan from L‐tryptophan (1). MarG/I convert 1 into (2S, 3R)‐β‐methyltryptophan, while MarG/I combined with MarH convert 1 into (2S, 3S)‐β‐methyltryptophan. MarH serves as a stereochemical switch by catalyzing the stereoinversion of the β‐stereocenter.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>